Clinical and Demographic Characteristics Differences between M. tuberculosis and M. bovis Infection in Bronchoalveolar Lavage Pulmonary TB Patients, Indonesia - Budi Yanti; Soetjipto Soetjipto; Ni Made Mertaniasih; Muhammad Amin (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: Some species of the Mycobacterium tuberculosis complex (MTBC) which can cause tuberculosis, particularly M. tuberculosis and M. bovis, may have different virulence property and therefore associated with various clinical severity in tuberculosis (TB) patients. The aim of this study was to determine the differences in clinical and demographic characteristics between M. tuberculosis and M. bovis infection among Indonesian TB patients. Methods: Thirty-one new and active TB patients were confirmed to have acid fast bacilli (AFB) sputum positive and/or Xpert MTB/RIF positive for M. tuberculosis from Dr. Soewandhie Hospital, Surabaya, Indonesia. Interviews were conducted to record the clinical and demographics required. The MTBC were isolated from bronchoalveolar lavage fluid (BALF) and determined by primer-specific PCR targeting TbD1 and RD9 region gene. The degree of lung tissue damage was classified using NICE Scoring System. Results: The MTBC were detected in all patients on whom 19 and 12 isolates were classified as M. tuberculosis and M. bovis respectively. There was a different on 74.2% of productive age subjects (21-50 years) with M. tuberculosis infection (P